FAKTOR-FAKTOR YANG MEMPENGARUHI IBU RUMAH TANGGA MENGGUNAKAN BAHAN TAMBAHAN PANGAN (BTP) SINTETIS - Oktavia, Putri Darma; Faridah, Anni; Holinesti, Rahmi (Journal of Home Economics and Tourism, 2017)
This research was aimed to describe factors which was affecting housewives to use synthetic food additives in terms of the internal factor were knowledge and external factor socialization media. This was a descriptive research, the population was housewives at Jati, Padang, West Sumatera which was 2.762 people and Base on that population was 97 housewives were choosen responden. Technique of data collecting was done by using a questionnaire based on Gutman’s scale. Furthermore, the data was analyzed through descriptive analysis. The result of the research on the factors affected housewives for using the synthetic food additives showed that internal factors such as knowledge of housewives about synthetic food additives was low which was 84 people with the percentage 86.6%. External factor of media sosialization affected housewives for using synthetic food additives was high which was 50 people with the percentage 51.55%.Keyword: synthetic food additives, Housewife